Atividade de sesquiterpenoides isolados de Nectandra grandiflora Nees sobre o sistema nervoso central - Garlet, Quelen Iane (2018)
Nectandra grandiflora (Lauraceae) is a native species from Rio Grande do Sul, Brazil, whose essential oil (EO) is rich in sesquiterpenoids, such as, (+)-dehydrofukinone (DHF), (-)-selin-11-en-4-alpha-ol (SEL), and the compounds of unprecedented chemical structures, (+)-eremophil-11-en-10-ol (ERM) and (+)-dehydrofukinone epoxide (DFX). The GABAergic system is the major target for the terpenoids that diminish the Central Nervous System (CNS) excitability. Therefore, this work aims to evaluate the interaction of DHF, SEL, ERM and DFX with the GABAa receptors. For this purpose, it was conducted an investigation of: (1) (10-3 - 102 μM) DHF and (0,1-100 μM) DFX, ERM and SEL effect on membrane potential and calcium mobilization in synaptosomes from mice cortex; (2) DHF (3; 10; 30 or 100 mg/kg) effect against pentylenetetrazole (PTZ; 50 mg/Kg, i.p.)-induced seizures in mice; (3) the long-term exposure to (12,5-25 mg/L) SEL-, ERM- and DFX-induced sedation on silver catfish (Rhamdia quelen); (4) the anxiolytic potential (open field and elevated plus maze tests) of the EO and isolated compounds DHF SEL, ERM e DFX (10, 30 e 100 mg/ kg, v.o.) in mice; (5) the involvement of the GABAa receptors in the actions of the EO and compounds on the CNS; (6) the compounds presence in the mice cerebral cortex by gas chromatography. Experimental protocols were approved by the Animal Ethics Committee of Federal University of Santa Maria. Results showed that: DHF, DFX, ERM and SEL facilitate the membrane hyperpolarization and inhibit the downstream calcium influx in synaptosomes; DHF blunted PTZ-induced seizures in mice. EO and compounds induce anxiolytic effects in mice; SEL, ERM e DFX induce persistent sedation in fish; EO induced an increase in the GABAa/α2 subunit expression, SEL increase the GABAa/ β1, δ and γ2 subunits expression, while the compound ERM decrease the GABAa/α1 subunit expression in silver catfish; The CNS effects displayed by the N. grandiflora EO and compounds are mostly due to their interaction with GABAa receptors. However, we did not rule out the possibility of other molecular targets. These thesis results improved the pharmacological characterization of N. grandiflora, whose EO and isolated compounds may be useful as sedatives on fish farming procedures and indicating a therapeutic potential of this species for the treatment of CNS pathologies, such as epilepsy and anxiety disorders.